Metaphors in Personal Narratives about Tinnitus: A Case Study of the American Tinnitus Association - Sintaningsih Utami; Ni Gusti Ayu Roselani (Hasanuddin University, 2025)
This study explores the metaphors utilized to describe the lived experience of tinnitus in internet personal narratives. The study aims to identify the types of metaphors used by tinnitus sufferers to describe their experience and to analyse the conceptual frames underpinning these metaphors. Data were collected from publicly available online personal narratives on American Tinnitus Association Website and analyzed qualitatively. The findings reveal a range of metaphor types, including inhabitant metaphors, war metaphors, journey metaphors, and loss/robbery metaphors. Notably, tinnitus is often conceptualized as an unwanted inhabitant, a stubborn intruder, or even as a predatory creature, reflecting its persistent and invasive nature. While based on a limited sample, this study provides valuable insights into the range of metaphorical expressions used by tinnitus sufferers and makes a meaningful contribution to understanding the role of metaphor in constructing and communicating subjective experiences of chronic health condition.